Enhancing patient-centered care: Evaluating quality of life in type 2 diabetes management - Branka Vlahovic; Vivek Jha; Vukasin Stojanovic; Tanja Vojinovic; Arshiya Dutta; Pinaki Dutta; Sanja Medenica (PLoS ONE, 2025)
Aims To evaluate quality of life (QoL) in patients with type 2 diabetes mellitus (T2DM). Methods A cross-sectional study included 151 T2DM patients at the Clinical Centre of Montenegro. The Ferrans and Powers Quality of Life Index (QLI), validated for the Montenegrin population, assessed QoL across five domains. Participants rated items on a Likert scale from 1 (very dissatisfied) to 5 (very satisfied). Data were analysed using SPSS version 22. Results The cohort included 51% women, with a mean age of 60.05 ±  11.63 years. Of the patients, 42% had diabetes for over a decade, and 64% had no additional health conditions. Overall, patients reported satisfactory QoL, especially in self-care and glucose management, though dissatisfaction was high regarding sexual life. Emotional support from family, housing, and friendships significantly contributed to life satisfaction, while financial concerns and job dissatisfaction were common. QoL showed no significant gender differences but declined with age and was notably lower in patients with comorbidities. Conclusion Patients with T2DM report generally satisfactory QoL, with notable concerns in socio-economic and health-related areas. Routine QoL assessments in clinical practice can improve communication, aid in early complication detection, and enable timely interventions to enhance patient outcomes.